2021
DOI: 10.1111/jrh.12628
|View full text |Cite
|
Sign up to set email alerts
|

Increasing access to care for trauma‐exposed rural veterans: A mixed methods outcome evaluation of a web‐based skills training program with telehealth‐delivered coaching

Abstract: Purpose: While rural veterans with trauma exposure report high rates of posttraumatic stress disorder (PTSD), depression, and functional impairment, utilization of health services is low. This pilot study used mixed qualitative and quantitative methods to evaluate the potential benefits of a transdiagnostic web-based skills training program paired with telehealth-delivered coaching to address a range of symptoms and functional difficulties. The study directed substantial outreach efforts to women veterans who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…For example, it is possible that self-guided work and the therapist sessions made unique and complementary contributions to the program outcomes and may ultimately have provided greater benefits than therapist-only or internet-only approaches [ 18 ]. Evidence for this view is supported by qualitative analyses from interviews completed in one of our earlier studies [ 21 ], which found that the self-guided work facilitated a sense of autonomy and mastery, while the therapist sessions provided emotional and practical support as well as clarity in tailoring the tools to specific problems and life experience. The potential presence of a dynamic, reciprocal relationship between these 2 treatment components deserves further investigation via assessment of cross-lagged effects and identification of underlying mechanisms of change.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, it is possible that self-guided work and the therapist sessions made unique and complementary contributions to the program outcomes and may ultimately have provided greater benefits than therapist-only or internet-only approaches [ 18 ]. Evidence for this view is supported by qualitative analyses from interviews completed in one of our earlier studies [ 21 ], which found that the self-guided work facilitated a sense of autonomy and mastery, while the therapist sessions provided emotional and practical support as well as clarity in tailoring the tools to specific problems and life experience. The potential presence of a dynamic, reciprocal relationship between these 2 treatment components deserves further investigation via assessment of cross-lagged effects and identification of underlying mechanisms of change.…”
Section: Discussionmentioning
confidence: 87%
“…The 1:1 ratio was adopted as the anchoring reference point for this investigation based on the high patient satisfaction ratings and the large effect sizes reported in the first webSTAIR study, which used this ratio [ 15 ], and because this ratio provided the maximum number of therapist sessions in a blended therapy program in which the intervention of interest was the web-based intervention. The selection of the 1:2 ratio was based on a pilot study that delivered webSTAIR with this ratio, yielding significant symptom reduction with a large effect size [ 21 ]. That study also included posttreatment interviews that identified an association between patient satisfaction and the number of therapist sessions; veterans reported in the interviews that self-guided work fostered independence and mastery.…”
Section: Introductionmentioning
confidence: 99%
“…Using video to conduct exposure treatments has expanded treatment possibilities in ways that neither phone nor in person modalities can: providers were able to view patients' home environments to better understand patients' symptoms and could teach patients how to do exposure treatment in their home environment [50]. Because of the unique aspects of treatments related to OCD and tic disorders, video may be preferable to phone, as it allows providers to collect collateral information from patients and tailor exposure protocols to patients' homes.…”
Section: Obsessive Compulsive and Tic Disorders (Ocd)mentioning
confidence: 99%
“…For example, it is possible that self-guided work and the therapist sessions made unique and complementary contributions to the program outcomes and may ultimately have provided greater benefits than therapist-only or internet-only approaches [18]. Evidence for this view is supported by qualitative analyses from interviews completed in one of our earlier studies [21], which found that the self-guided work facilitated a sense of autonomy and mastery, while the therapist sessions provided emotional and practical support as well as clarity in tailoring the tools to specific problems and life experience. The potential presence of a dynamic, reciprocal relationship between these 2 treatment components deserves further investigation via assessment of cross-lagged effects and identification of underlying mechanisms of change.…”
Section: Discussionmentioning
confidence: 85%